Transformation of The Giver Novel into Film by Phillip Noyce - Sholihah, Alimah B.; Setiawan, Ikwan; Kusumayanti, Dina D. (English Department, Faculty of Humanities, Andalas University, 2024)
There are numerous ways to adapt a literary work. One of them is adaptingliterary work from the novel into the film. This article is about LoisLowry’s novel The Giver, which was adapted into a film with the sametitle by Phillip Noyce. During the adaptation process, transformations inthe intrinsic elements were discovered. This transformation can occur dueto differences in media, which was originally in the form of text (novel) toaudiovisual (film). This article aims to discover the transformations thatoccurred during adaptation as well as the motive of the adapter. Severalsteps were taken to accomplish this goal. The first step is to classify thediscovered differences into tables. The transformations are then analyzedin the second step to determine the visible ideology. Third, the adapter’smotives can be identified using the ideology that has been discovered. Thetheory of adaptation and mythology is the one employed in this article.In order to identify ideology, the mythology theory is used to analyzedifferences. Afterward, using the identified ideology, the adapter’s motivesare discovered using the adaptation theory. The final result of the adaptationof The Giver novel depicted several ideologies including totalitarianism,liberalism, and freedom. The visible motives are personal and politicalmotives and economic lures.